ANALISIS KEMAMPUAN GURU FIKIH DALAM MELAKSANAKAN PENILAIAN KURIKULUM 2013 DI MIS MAURA EL MUMTAZ KELURAHAN TANAH SERIBU KECAMATAN BINJAI SELATAN KOTA BINJAI - Dandi Irawan; Siti Halimah (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Curriculum evaluation in the CIPP model is intended to compare the performance of various program dimensions with a number of certain criteria to produce judgments or considerations regarding the strengths and weaknesses of the curriculum. What are the assessment standards for geography learning at MIS Maura el Mumtaz, Tanah Seribu Village, South Binjai District, Binjai City. 2. What is the suitability of the implementation of the 2013 curriculum assessment standard in geography learning at MIS Maura el Mumtaz, Tanah Seribu Village, South Binjai District, Binjai City.